Prescription pattern at outpatient department in a tertiary care hospital of Gujarat: a cross-sectional study - Gohil, Nayana J. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Evaluation of drug prescription prototype is a significant feature of patient care, which also provides as an estimate of the quality of care provided. Thus, the current study was carried out to analyze the prescriptions of patients attending outpatient department (OPD) of a tertiary care teaching hospital. Methods: Present cross-sectional study was performed in the OPD of our tertiary care teaching hospital. The study was carrying out for duration of two years. Data was obtained from 850 prescriptions. Data was analysed as per WHO prescribing indicators. Results: Total 1700 prescriptions were analysed, that includes 55.8% males and 40.1% females. The highest numbers of prescriptions were from the age group of 18-40 (53.6%) years of age. Average number of drugs in the current study was found to be (2.1). Percentage of come across with an antibiotic prescribed was 17.12%. Percentage of come across with an injection prescribed was 11.81%. Conclusions: There is necessitate of recuperating the prescribing pattern by maintaining the number of medicines as little as possible, prescribing medicines by generic names, using medicines properly after selecting and deliberately keeping the charge of treatment low.